2015
DOI: 10.1177/1933719114537713
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Trimester Maternal ADAM12 Levels Differ According to Fetal Gender in Pregnancies Complicated by Preeclampsia

Abstract: An overrepresentation of adverse pregnancy outcomes has been observed in pregnancies associated with a male fetus. We investigated the association between fetal gender and candidate biomarkers for preeclampsia. Proteins were quantified in samples taken at 20 weeks from women recruited to the SCreening fOr Pregnancy Endpoints (SCOPE) study (preeclampsia n ¼ 150; no preeclampsia n ¼ 450). In contrast to placental growth factor, soluble endoglin, and insulin-like growth factor acid labile subunit, levels of metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
(55 reference statements)
1
10
1
Order By: Relevance
“…Excessive inflammation is implicated in preeclampsia pathogenesis. 7,11,18 This is an avenue that should be examined further as antiangiogenic biomarkers are linked to placental phenotypes of preeclampsia. 3,5,15 Alternatively, studies have shown that fetuses respond differently to maternal inflammatory insults.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Excessive inflammation is implicated in preeclampsia pathogenesis. 7,11,18 This is an avenue that should be examined further as antiangiogenic biomarkers are linked to placental phenotypes of preeclampsia. 3,5,15 Alternatively, studies have shown that fetuses respond differently to maternal inflammatory insults.…”
Section: Introductionmentioning
confidence: 99%
“…7,11,18 This is an avenue that should be examined further as antiangiogenic biomarkers are linked to placental phenotypes of preeclampsia. 7 Fetal sex could influence levels of antiangiogenic markers altering the risk of preeclampsia. 19,20 Both biomarkers may cause endothelial dysfunction, sFLT by impairing endothelial growth factor 21 and endoglin by impairing transforming growth factor signaling.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations